2007
DOI: 10.1097/01.cji.0000211331.61019.26
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antitumoral Activity of Baculovirus-expressed Chimeric Recombinant Anti-CD4 Antibody 13B8.2 on T-cell Lymphomas

Abstract: A baculovirus-expressed chimeric recombinant IgG1 (rIgG1) antibody, with Cgamma1 and Ckappa human constant domains, was derived from the murine monoclonal antibody 13B8.2, which is specific for the CDR3-like loop of the CD4 molecule. The recombinant IgG1 antibody 13B8.2 was previously shown to inhibit HIV-1 replication and to abrogate the one-way mixed-lymphocyte reaction and block proliferation of CD3-stimulated peripheral blood CD4 lymphocytes from healthy donors. Before testing this recombinant anti-CD4 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Recombinant IgG 1 Ab 13B8.2 (rIgG 1 13B8.2) has been proposed as a potential therapeutic agent for the treatment of CD4 ϩ malignant diseases because it induces complement-mediated lysis, Abdependent cell cytotoxicity, and growth arrest of T lymphoma cells (22). We demonstrated in this study that the baculovirus-expressed rIgG 1 13B8.2 Ab acts by causing the accumulation of the CD4 molecule inside the Brij 98-extracted rafts and by excluding the Zap70 kinase and downstream targets SLP-76, PLC␥1, and Vav-1 from the raft machinery, together with affecting Zap70 phosphorylation, which impairs further downstream activation events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant IgG 1 Ab 13B8.2 (rIgG 1 13B8.2) has been proposed as a potential therapeutic agent for the treatment of CD4 ϩ malignant diseases because it induces complement-mediated lysis, Abdependent cell cytotoxicity, and growth arrest of T lymphoma cells (22). We demonstrated in this study that the baculovirus-expressed rIgG 1 13B8.2 Ab acts by causing the accumulation of the CD4 molecule inside the Brij 98-extracted rafts and by excluding the Zap70 kinase and downstream targets SLP-76, PLC␥1, and Vav-1 from the raft machinery, together with affecting Zap70 phosphorylation, which impairs further downstream activation events.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated a recombinant Ab (17,18) derived from the 13B8.2 murine anti-CD4 mAb, directed against the CDR3-like loop of CD4; this loop has not been fully exploited as a target by clinical Abs, mainly directed against other CD4 regions (11-13, 19, 20). This baculovirus-expressed recombinant Ab (rIgG 1 ) inhibits HIV replication at a post-gp120-binding step (17,18,21) and induces complement-mediated lysis, Ab-dependent cell cytotoxicity, and growth arrest of T lymphoma cells (22). The biological effects of rIgG 1 13B8.2 are partly due to signals that prevent NF-B nuclear translocation (23); ERK activation (24); and NF-AT, NF-B, and AP-1 binding to the IL-2 gene promoter (25).…”
mentioning
confidence: 99%
“…Phosphatidylserine externalization in cells undergoing death receptor-mediated apoptosis seems to be Ca ++ -dependent [36]. Our finding that rIgG 1 13B8.2 lowers phosphatidylserine level in Jurkat T cells explains why treatment with rIgG 1 13B8.2 did not induce phosphatidylserine-dependent apoptosis in T cell lymphomas [19] and blocked CD3-induced Ca ++ increase and the subsequent signaling pathways [33]. Similarly, other CD4-specific antibodies have been shown to modulate phosphatidylserine level in vitro [37].…”
Section: Discussionmentioning
confidence: 49%
“…Analysis of key upstream events showed that modulation of ZAP-70 Tyr 292 and Tyr 319 phosphorylation occurred concomitantly with rIgG 1 13B8.2-induced ZAP-70 exclusion from the membrane rafts [16]. Such antibody-induced modulation of membrane raft signaling, which leads to inhibition both of NF-B nuclear translocation [17] and of binding to the IL2 gene promoter [18], partly explains the anti-proliferative effect of rIgG 1 13B8.2 in T cell lymphomas [19]; however the effects of rIgG 1 13B8.2 on lipid dynamics in membrane rafts remain unknown. Therefore, we decided to examine the effects of the anti-CD4 rIgG 1 13B8.2 antibody on the lipid composition of membrane rafts in a T lymphoma cell line.…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies investigating CDC activity of IgG antibodies produced in insect cells. 23,26,27,100 In several cases, no CDC activation could be demonstrated, but this was true also for the parent antibody produced in mammalian cells. 23,26 In one study, insect cell produced antibodies could indeed induce C1q binding or CDC with human serum.…”
Section: Glycosylation In Insect Cellsmentioning
confidence: 95%